Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s10688-005-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

On the inverse of the generator of a bounded C 0-semigroup

Abstract: Let A be the generator of a uniformly bounded C 0 -semigroup in a Banach space B , and let A have a densely defined inverse A −1 . We present sufficient conditions on the resolvent (A−λI) −1 , Re λ > 0, under which A −1 is also the generator of a uniformly bounded C 0 -semigroup.Key words: uniformly bounded C 0 -semigroup, inverse of the generator, Banach space, Carleson embedding theorem. 1.Let B be a Banach space with norm · , and let E = E(B) be the set of densely defined closed linear operators in B. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…So, the Theorem provides the example of a nilpotent C 0 -semigroup It can also be shown that in this case (see [8,9]) the semigroup (e tA −1 ) t≥0 has the following integral representation:…”
Section: Comments and Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the Theorem provides the example of a nilpotent C 0 -semigroup It can also be shown that in this case (see [8,9]) the semigroup (e tA −1 ) t≥0 has the following integral representation:…”
Section: Comments and Remarksmentioning
confidence: 99%
“…On the other hand, it was shown in [8,9,11,12] that there exists a Banach space X and an injective linear operator on X with dense range generating a uniformly bounded C 0 -semigroup whose inverse does not generate a C 0 -semigroup. In [9] this was proved for X = l p , p ∈ (1, 2) ∪ (2, ∞).…”
Section: Comments and Remarksmentioning
confidence: 99%
“…Recently, Piskarev, Zwart [16] proved that this result (and even the estimate V n (V − I) ≤ c(1 + √ n)) is optimal. On the other side, Gomilko, Zwart, Tomilov [9] showed that on every l p -space, 1 < p < ∞, p = 2 there exists a contraction V with 1 / ∈ P σ (V) which is not the cogenerator of a C 0 -semigroup. An analogous example on the space c 0 follows from Komatsu [13, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Note that although the proofs in this section are easy, the presented method seems to be promising. We also discuss the connection with the inverse of a generator and growth of the corresponding semigroup (see Zwart [21,22] Gomilko, Zwart [10], Gomilko, Zwart, Tomilov [9], de Laubenfels [14] for this aspect).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for every p ∈ [1, 3 ) ∪ (4, ∞) he constructed a bounded generator of a contraction semigroup on ℓ p , such that the inverse does not generate a C 0 -semigroup, see [8], thus proving that the question by deLaubenfels should be answered negatively on reflexive Banach spaces and for bounded generators. Furthermore, in [7] he gives some sufficient conditions under which A −1 is also a infinitesimal generator of a bounded C 0 -semigroup.…”
mentioning
confidence: 99%